2014
DOI: 10.4103/0973-1482.136658
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of cavernous haemangioma of the Fallopian tube

Abstract: Fallopian tubes are one of the uncommon sites for neoplastic lesions in the female genital tract. Haemangiomas of the fallopian tubes are rare benign neoplasms that are documented as isolated case reports only. We present a rare case of incidentally detected cavernous haemangioma of the fallopian tube in a post menopausal female who underwent hysterectomy and bilateral salphingoopherectomy for dysfunctional uterine bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It is commonly believed that FT hemangioma is associated with the effect of estrogens, which stimulate the growth of blood vessels. This has been confirmed in some cases in which estrogen receptors were found in the endothelial cells of hemangiomas during immunohistochemical studies 1 , 2 , 3 , 6 , 8 , 10 . This case’s postoperative material study demonstrated the absence of estrogen receptors in the endothelial tumor cells, which indicates that the occurrence and growth of the FT hemangioma did not depend on the effect of estrogen.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…It is commonly believed that FT hemangioma is associated with the effect of estrogens, which stimulate the growth of blood vessels. This has been confirmed in some cases in which estrogen receptors were found in the endothelial cells of hemangiomas during immunohistochemical studies 1 , 2 , 3 , 6 , 8 , 10 . This case’s postoperative material study demonstrated the absence of estrogen receptors in the endothelial tumor cells, which indicates that the occurrence and growth of the FT hemangioma did not depend on the effect of estrogen.…”
Section: Discussionmentioning
confidence: 53%
“…FT hemangioma is a sporadic benign vascular tumor, with only 16 documented cases available in the literature. Most of these neoplasms measured between 2 and 10 mm, had no clinical manifestations, and were incidentally discovered during surgeries for other diseases 1 , 6 , 9 . Thus, it should be assumed that the incidence of FT hemangioma is much higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mostly, presenting as a small nodule or bulge in tubal wall. 2,3,[6][7][8] However, in few cases the lesion was found inside the tubal lumen filling it as hemorrhagic mass. [9][10][11] In the present case, the lesion was present in left fallopian tube and the tube was grossly normal.…”
Section: Discussionmentioning
confidence: 99%